Baicalein attenuates hypertrophic scar formation via inhibition of the transforming growth factor‐β/Smad2/3 signalling pathway. (8th November 2015) - Zhang, Y.F.; Zhou, S.Z.; Cheng, X.Y.; Yi, B.; Shan, S.Z.; Wang, J.; Li, Q.F.
Summary: Background: Hypertrophic scars (HPSs) are characterized by excessive fibrosis associated with aberrant function of fibroblasts. Currently no satisfactory treatment has been developed. Objectives: To investigate the effect of baicalein on HPSs and its underlying mechanisms. Methods: Baicalein was administered intradermally (10 μmol L −1 in 100 μL sterile saline plus 10% dimethylsulfoxide) to mechanical‐load‐induced scars in mice once a day for 14 or 28 days. Histological and immunohistochemical studies were performed to evaluate scar hypertrophy and the function of fibroblasts. Human HPS‐derived fibroblasts (HSFs) were determined by immunofluorescence study, collagen gel contraction assay and wound‐healing assay. Also, protein expression of the transforming growth factor (TGF)‐β signalling pathway was detected using Western blotting. Lastly, a molecular docking study and kinase binding assay were conducted in search of the potential interaction between baicalein and activin receptor‐like kinase (ALK)5. Results: Baicalein treatment significantly attenuated HPS formation and collagen deposition in a mechanical‐load‐induced mouse model. Baicalein also inhibited the proliferation and activation of fibroblasts in vitro and in vivo . Furthermore, baicalein impaired the contractile and migration ability of HSFs. Protein expression investigation revealed that baicalein had an inhibitory effect on TGF‐β/Smad2/3 signalling. Such bioactivity of baicalein may result from its selective binding to the ATP‐binding pocket of ALK5, as suggested by the molecular docking study and kinase binding assay. Conclusions: Baicalein could serve as a promising agent for treatment of HPSs and a selective ALK5 inhibitor. Abstract : What's already known about this topic? Hypertrophic scars (HPSs) are characterized by excessive fibrosis associated with aberrant proliferation and activation of fibroblasts. The transforming growth factor (TGF)‐β signalling pathway has been shown to play a crucial role in HPS formation. What does this study add? Baicalein attenuates HPSs by suppressing the proliferation, activation, contraction and migration of fibroblasts. Baicalein could bind to activin receptor‐like kinase 5 and consequently inhibit TGF‐β/Smad2/3 signalling.